The Multicultural Leadership Model of School Administrators under the Yala Primary Educational Service Area Office 2 - Saemasae, Nursahida; Kao-ian , Jarunee; Suwanno , Phimpawee (Al-HIKMAH Journal, 2024)
The objectives of this research were to 1) study condition and the model of multicultural leadership of school administrators under the Yala Primary Educational Service Area Office 2, and 2) create the model of multicultural leadership of school administrators under the Yala Primary Educational Service Area Office 2. The research process consisted of two steps. Step 1: studying documents and research related to multicultural leadership to obtain the interview topics and collect qualitative data using semi-structured interviews with 11 participants were conducted. Step 2: proceeding with the draft model of multicultural leadership to three qualified experts for validation and content validity assessment were executed. The index of item objective congruence (IOC) of three experts ranged from 0.67 to 1.00 with a confidence level of .987. After validation, the model of multicultural leadership was applied to 315 samples, and data analysis was conducted by using statistical software package to calculate means and standard deviations. The results revealed that: Phase 1: the condition and model of multicultural leadership of school administrators under the Yala Primary Educational Service Area Office 2 involved five aspects including 1) accepting cultural diversity, 2) having communication ability, 3) developing relationships among people in the organization, 4) supporting resources, and 5) morality aspect. Phase 2: the model of multicultural leadership of school administrators under the Yala Primary Educational Service Area Office 2 comprised five aspects: 1. Accepting cultural diversity involved 1) school administrators participated in and supported various cultural activities, 2) school administrators promoted and participated in community activities, and 3) school administrators showed enthusiasm and interest in learning about cultural differences amidst diversity for overall success. 2. Having communication ability included 1) school administrators spoke politely, gently, and sincerely with teachers and staff,2) school administrators attentively listened, empathized, accepted others’ viewpoints, and treated others well, and 3) school administrators provided guidance helping teachers and staff to improve their capabilities. 3. Developing relationships among people in the organization consisted of 1) school administrators built good relationships with individuals within and outside the organization, 2) school administrators provided opportunities for teachers and staff to express opinions and made decisions regarding various process, and 3) school administrators understood oneself and others, and accepted differences among individuals. 4. Supporting resources included 1) school administrators promoted and supported resources for curriculum development aligning with the school’s context, 2) school administrators developed curriculum using local resources according to community needs, and 3) school administrators participated in community engagement as a multicultural learning resource development. 5. Morality aspect included 1) school administrators held firm intention of good governance principles in managing internal organizational affairs, 2) school administrators mediated conflicts or problems among teachers and staff, and 3) school administrators demonstrated sacrifice and devotion to the organization from beginning to end. When assessing for the appropriateness of implementation, it was found that the overall and individual aspects were at a high level.